AIMETA 2005 Atti del XVII Congresso dell'Associazione italiana di meccanica teorica e applicata. Firenze, 11-15 settembre 2005. Volume II - Borri, Claudio; Facchini, Luca; Federici, Giorgio; Primicerio, Mario (Proceedings e report, 2006)
The volume collects the contributions presented at the XVII national congress of AIMETA which, for technical reasons, did not find space in the first volume dedicated to the proceedings of the congress. The new texts complete the picture of the current situation and future prospects of Mechanics that emerged from the congress held in Florence.